2021
DOI: 10.3389/fpls.2021.667060
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Chloroplast Genome of Plukenetia volubilis Provides Insights Into the Organelle Inheritance

Abstract: Plukenetia volubilis L. (Malpighiales: Euphorbiaceae), also known as Sacha inchi, is considered a promising crop due to its high seed content of unsaturated fatty acids (UFAs), all of them highly valuable for food and cosmetic industries, but the genetic basis of oil biosynthesis of this non-model plant is still insufficient. Here, we sequenced the total DNA of Sacha inchi by using Illumina and Nanopore technologies and approached a de novo reconstruction of the whole nucleotide sequence and the organization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Besides, our findings revealed that the total length, GC content, and gene composition of the cp genomes were almost identical in all species. Previous studies have shown that the cp genome of angiosperms is highly conserved at the genus level (Khan et al, 2020;Villanueva-Corrales et al, 2021;Feng et al, 2022). Moreover, previous research demonstrated that the rps19 gene existed in the IR region (Ahmed et al, 2012;Wang et al, 2022).…”
Section: Cp Genome Structure and Comparative Analysismentioning
confidence: 99%
“…Besides, our findings revealed that the total length, GC content, and gene composition of the cp genomes were almost identical in all species. Previous studies have shown that the cp genome of angiosperms is highly conserved at the genus level (Khan et al, 2020;Villanueva-Corrales et al, 2021;Feng et al, 2022). Moreover, previous research demonstrated that the rps19 gene existed in the IR region (Ahmed et al, 2012;Wang et al, 2022).…”
Section: Cp Genome Structure and Comparative Analysismentioning
confidence: 99%
“…Chloroplasts are key plant organelles that are involved in photosynthesis and important biological processes, such as fatty acid and amino acid synthesis ( Sugiura, 1992 ). The chloroplast genome of higher plants is a double-stranded and circular DNA molecule with a typical quadripartite structure ( Dong et al, 2013 , 2021a ; Villanueva-Corrales et al, 2021 ), including a pair of inverted repeats (IRs) as well as a large single copy (LSC) and a small single copy (SSC) region. The chloroplast genome encodes approximately 80 protein-coding, 30 transfer RNA (tRNA), and four ribosomal RNA (rRNA) genes, and the structure of the chloroplast genome, including the gene content and gene order, is conserved.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the structure and organization of the nine observed cp genomes in Thalictrum , including T. fargesii , follow the typical structure commonly found in angiosperms, except for a difference in tRNA content in T. viscosum , which contains 38 tRNAs instead of 37 ( Park et al., 2015 ; Daniell et al., 2016 ; He et al., 2019 ; Morales-Briones et al., 2019 ; He et al., 2021 ; Cai et al., 2022 ; Zhe et al., 2023 ). The total length, GC content, and gene composition were almost identical in the cp genomes of all studied species, and these highly conserved features might be due to a typical evolutionary passage in Thalictrum ( Khan et al., 2020 ; Villanueva-Corrales et al., 2021 ; Feng et al., 2022 ). Compared to the LSC and SSC regions, the IR region was more conserved among the cp genomes.…”
Section: Discussionmentioning
confidence: 83%